EFFECT OF FREEZING AND THAWING PROCESSES ON SOIL AGGREGATE STABILITY - Oztas T.; Fayetorbay F. (My University, 2003)
The effect of freezing and thawing on wet aggregate stability of soils formed on different parent materials was determined for different aggregate size groups (0.0-1.0; 1.0-2.0; and 2.0-4.0 mm), different water contents and for various freezing and thawing cycles (three, six and nine times) and freezing temperatures (-4 and -18 °C). The initial wet aggregate stability decreased with freeze-thaw treatments by 28.6-51.7% depending on soil type, and was more pronounced with increased moisture contents at freezing. The percent decrease in wet aggregate stability for different aggregate size groups ranged from 13.8% to 57.7%. Wet aggregate stability generally increased when the number of freezing and thawing cycles increased from 3 to 6, but decreased after that point. The percentage of water-stable aggregates in all soils at -18 °C was less than that at -4 °C.
Keywords: AGGREGATE STABILITY; FREEZING-THAWING; SOIL STRUCTURE